Проблема трудоустройства женщин в украине в связи с дискриминацией по гендерному признаку - Роговец, В. Е.; Чекубашева, В. А. (ХНУРЕ, 2019)
Nowadays it seems that gender discrimination problems are the case of days gone by, nevertheless they exist at present. Despite their existence is constantly being rejected they still make life harder to a lot of people. One of these problems in Ukraine is a problem of women employment, within gender discrimination. Despite the efforts of various organizations, women still remain unprotected contrary to the laws. There are still “non-female” professions and a host of other arguments getting round the constitution of Ukraine. This work is aimed to draw attention to it and to suggest the ways of its decision